Revision of the Afrotropical genus Afrepipona Giordani Soika, 1965 and description of Afrepsilon gen. nov. (Hymenoptera: Vespidae: Eumeninae) - Selis, Marco; Carpenter, James M. (European Journal of Taxonomy, 2024)
A taxonomic study on the Afrotropical genera Afrepipona Giordani Soika, 1965 and Afrepsilon gen. nov. is presented. Twenty new species are described, of which 15 are in Afrepipona (Afrepipona anomala sp. nov., Afrepipona cellularis sp. nov., Afrepipona clonata sp. nov., Afrepipona cuprea sp. nov., Afrepipona lamellata sp. nov., Afrepipona lamptula sp. nov., Afrepipona lobulata sp. nov., Afrepipona meridionalis sp. nov., Afrepipona occidentalis sp. nov., Afrepipona orientalis sp. nov., Afrepipona punctatissima sp. nov., Afrepipona scabra sp. nov., Afrepipona segregata sp. nov., Afrepipona ulterior sp. nov., Afrepipona vulcanica sp. nov.) and five are in Afrepsilon (Afrepsilon aterrimum gen. et sp. nov., Afrepsilon ferrugineoaureum gen. et sp. nov., Afrepsilon hybridum gen. et sp. nov., Afrepsilon minor gen. et sp. nov., and Afrepsilon pictum gen. et sp. nov.). Afrepipona lamptoensis Giordani Soika, 1965 is withdrawn from synonymy with A. angusta (de Saussure, 1863) and subsequently revalidated. Afrepipona unifasciata Gusenleitner, 2012 is transferred to the genus Antodynerus de Saussure, 1855 (Antodynerus unifasciatus comb. nov.). Keys to all known species are provided.